Assessment of Staling Aldehydes in Lager Beer under Maritime Transport and Storage Conditions - Aguiar, Dayana (2022)
Beer flavor stability is greatly influenced by external temperature, vibrations, and longer delivery times. The present study assessed the impact of transport and storage conditions on staling aldehyde evolution in lager beers across five sample groups (fresh, transport, and storage simulation, and their controls), which differed in their bottle opening system (either crown cap or ring pull cap). Maritime transport conditions (45 days of travel, vibrations of 1.7 Hz, and warm temperatures (21-30 °C)) were simulated, together with storage time in a distributor's warehouse (up to 75 days). The results revealed that the concentration of Strecker aldehydes increased more quickly after transport and storage simulation in beer bottles with the ring pull cap opening system, and the contents of 2-methylpropanal and 3-methylbutanal, in particular, were up to three times higher. Benzaldehyde content also increased significantly, by 33% on average, in these samples. Hexanal was only found in beers with a ring pull cap that underwent transport simulation. Further storage after transport simulation significantly reduced the content of 2-methylpropanal, 3-methylbutanal, and hexanal, by 73%, 57%, and 43%, respectively, suggesting the formation of a bound state. 5-hydroxymethylfurfural was continuously increased by 78.5% and 40.5% after the Transport and Transport & Storage simulations, respectively. Transport conditions lead to a slight increase, of 0.6 EBC units, in beer color.